Guinea pigs add up - Cuyler, Margery (Walker Books for Young Readers : Distributed to the trade by Macmillan, 2010)
Mr. Gilbert brings in a guinea pig as a class pet, but it looks so lonely he brings another, and before long the class is getting an unexpected lesson in addition--and a very full cage.